Knowledge, Attitude and Practice of Healthcare Workers Towards Availability of Antiretroviral Pre-Exposure Prohylaxis in Nigeria - Joseph Afe Abayomi; Adetula Adefunke; Peter Olugbemiga; Ebenezer Oluwalusi; Olonisakin Omolola (Journal of Clinical Research In HIV AIDS And Prevention, 2018)
Introduction: The introduction of preexposure prophylaxis (PrEP) against incident HIV infection has changed the epidemiology of disease as continuous treatment with tenofovir and emtricitabine among high risk groups can reduce the relative risk for incident HIV infection by over 90%.However,despite the approved use of TDF+FTC, as a fixed dose combination of emtricitabine 200 mg and tenofovir disoproxil fumarate 300 mg, for oral PrEP since 2012 , it does not appear to have become widely accepted and in use among healthcare workers especially those in low income countries. Researches are therefore needed to consider the awareness and practice of health workers towards the availability of PrEP services in this part of the world. Healthcare workers are expected to be promoters of the use of PrEP services. Method: A cross sectional questionnaire-based study conducted in southern Nigerian over a 6 months period. Data were collected from 250 healthcare workers using interviewer-administered questionnaires. The data analysis was done using statistical package for the social sciences (SPSS) for windows version 20.0 software (SPSS Inc; Chicago, IL, USA). Frequency counts were generated for all variables and statistical test of significance was performed with chi-square test. Significance was fixed at P < 0.05 and highly significance if P < 0.01. Results: A high proportion of the respondents(>60%) were highly educated healthcare workers(majorly Nurses and medical doctors) and about half (55%) having at least 10yrs working experience in the health sector with most especially on the HIV program(>90%), majority (94%) of the health workers were aware about ARV pre-exposure prophylaxis but very few ( 6% )could give the standard definition for PrEP as the use of ARV drugs by HIV negative persons to prevent the acquisition of HIV.Most(67%) of them gave wrong definition for PrEP and worse still about one fifth (20%) had no idea what PrEP was all about. Most (70%) could not correctly identify all the ARV drugs in a standard PrEP regimen while about 35% had no idea at all of the approved ARVs used for PrEP. Though PrEP services was not available at any of the facilities where the respondents were working ,the approved drugs(TDF+FTC) for PrEP were available at about 40% of the health facilities(public and private) and 15% community pharmacies in the vicinity of the respondents . Only 60% of the respondents were willing to access PrEP service for themselves if indicated while 35% would not use such services even if it is indicated for reasons which include concern about adverse effects and safety.Awareness of PrEP was significantly associated with the ability of the healthcare workers to identify the correct ARV regimen, ARV dosages and also correct indication for PrEP. Awareness was also associated with the knowledge of the correct proven efficacy for PrEP(>95%) and high likelihood of seeing a patient placed on PrEP and willingness to use PrEP based on personal indication Conclusion: The level of awareness of PrEP among healthcare workers was very high at about 90% yet many(60%) could not give correct standard definitions of PrEP, PrEP ARV regimen, dosages and level of efficacy of PrEP. Also none of the respondent had PrEP services available either at their center or any known referral centers. This is unacceptable in a country with second highest HIV burden in the world and has adopted PrEP in her national HIV guideline with ongoing PrEP demonstration studies. The few healthcare workers who were able to mentioned this information were more likely to have seen a patient placed on PrEP and were more willing to use PrEP based on personal indication. Recommendations: There is need to deepen the and knowledge of PrEP among healthcare workers especially those in poor resource settings by engaging them through update courses outreach, educational resources, campaigns/seminars and workshops and various job aids. All healthcare service providers should be very comfortable to carry out HIV risk assessment of their clients and provide PrEP to those indicated directly or indirectly through referral
Keywords: preexposure prophylaxis (PrEP)